Unsettling sights : the fourth world on film - Columpar, Corinn, 1970- (UPCC book collections on Project MUSE., 2010)
Unsettling Sights: The Fourth World on Film examines the politics of representing Aboriginality, in the process bringing frequently marginalized voices and visions, issues and debates into the limelight. Corinn Columpar uses film theory, postcolonial theory, and Indigenous theory to frame her discussion of the cinematic construction and transnational circulation of Aboriginality. The result is a broad interdisciplinary analysis of how Indigeneity is represented in cinema, supported by more than twenty rigorous and theoretically informed case studies of contemporary feat.